Inactivation of the CovR/S virulence regulator impairs infection in an improved murine model of Streptococcus pyogenes naso-pharyngeal infection. - Faraz M Alam; Claire E Turner; Ken Smith; Siouxsie Wiles; Shiranee Sriskandan (PLoS ONE)
Streptococcus pyogenes is a leading cause of pharyngeal infection, with an estimated 616 million cases per year. The human nasopharynx represents the major reservoir for all S. pyogenes infection, including severe invasive disease. To investigate bacterial and host factors that influence S. pyogenes infection, we have devised an improved murine model of nasopharyngeal colonization, with an optimized dosing volume to avoid fulminant infections and a sensitive host strain. In addition we have utilized a refined technique for longitudinal monitoring of bacterial burden that is non-invasive thereby reducing the numbers of animals required. The model was used to demonstrate that the two component regulatory system, CovR/S, is required for optimum infection and transmission from the nasopharynx. There is a fitness cost conferred by covR/S mutation that is specific to the nasopharynx. This may explain why S. pyogenes with altered covR/S have not become prevalent in community infections despite possessing a selective advantage in invasive infection.